2007
DOI: 10.1007/s11664-007-0353-8
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Properties of High-Quality InN Nanowires and Nanonetworks

Abstract: We report on the growth of high-quality InN nanowires by the vapor-liquidsolid mechanism at rates of up to 30 lm/h. Smooth and horizontal nanowire growth has been achieved only with nanoscale catalyst patterns, while largearea catalyst coverage resulted in uncontrolled and three-dimensional growth. The InN nanowires grow along the [110] direction with diameters of 20 to 60 nm and lengths of 5 to 15 lm. The nanowires bend spontaneously or get deflected from other nanowires at angles that are multiples of 30°, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
22
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 25 publications
(30 reference statements)
2
22
0
Order By: Relevance
“…This could be partly due to the presence of a few-nanometer-thick indium oxide layer on the NW surface, which would underestimate the conductivity of the NWs by increasing the NW diameter used in our calculations compared to the actual diameter of the conducting core. Our TEM images have shown the presence of these oxide layers [22], which have been observed by other researchers as well [26]. For mobility calculations, the diameter appears in the logarithmic term in equation (3), so small deviations do not cause a significant error in the calculated mobility.…”
Section: ∼850supporting
confidence: 84%
See 1 more Smart Citation
“…This could be partly due to the presence of a few-nanometer-thick indium oxide layer on the NW surface, which would underestimate the conductivity of the NWs by increasing the NW diameter used in our calculations compared to the actual diameter of the conducting core. Our TEM images have shown the presence of these oxide layers [22], which have been observed by other researchers as well [26]. For mobility calculations, the diameter appears in the logarithmic term in equation (3), so small deviations do not cause a significant error in the calculated mobility.…”
Section: ∼850supporting
confidence: 84%
“…Examining the various images of the NWs, we found that they exhibit two distinctive properties: (i) they are almost always coplanar, especially when growing on the plane of the substrate, and (ii) they change their growth direction either spontaneously or upon meeting an obstacle in their growth path [22]. Figure 2(a) shows an example of spontaneous bending of the NW, where it bends five times, each time at an angle of ∼30…”
mentioning
confidence: 99%
“…1͑b͔͒. 2,13,14 Extrapolating the resistance of over 30 devices ͑not shown͒ to zero length, we obtained a contact resistance of 440 ⍀, which is nonnegligible compared to the lowest resistance in some of the nanowires and must be included in the modeling as discussed. 15 A schematic of the electrolyte gating setup is shown in Fig.…”
mentioning
confidence: 99%
“…2,14 We compare the mobility values of these three nanowires with Hall mobilities of InN thin films 20,21 in Fig. 3.…”
mentioning
confidence: 99%
“…However there have been serious issues regarding the quality of the NWs and control of the growth process. We have recently reported on the growth of high quality InN NWs along the substrate surface [20]. In this study, we have used these NWs to fabricate back-gated FETs, and measured the electrical transport properties.…”
Section: Introductionmentioning
confidence: 99%